What Influences Consumer Evaluation of Genetically Modified Foods?. (April 2019) - Pham, Nguyen; Mandel, Naomi
Genetically modified (GM) foods have attracted a great deal of controversy. While some consumers and organizations regard GM foods as safe, many other consumers and organizations remain concerned about their potential health risks. The results of three studies suggest that consumers respond differently to persuasive messages regarding GM foods on the basis of their preexisting attitudes. Weak anti-GM consumers tend to comply with a variety of pro-GM messages. In contrast, strong anti-GM consumers exhibit message-opposing behavior. Moreover, they respond just as negatively to a safety message (claiming that GM foods are safe) as to a risk message (claiming that GM foods are unsafe). The mechanism underlying these effects is consumers' perceived health risk. A benefit message claiming that GM foods are beneficial (e.g., more nutritious than their conventional counterparts) is a better alternative for strong anti-GM consumers. Finally, the results suggest that persuasive messages do not significantly change pro-GM consumers' evaluations of these foods.